Micro-mechanisms of deformation and strengthening during high pressure torsion of CoCuFeMnNi high entropy alloy - Sonkusare R.; Gurao N.P.; Biswas K.; Basu J.; Sen S.; Pradeep K.G.; Praveena M.; Bhowmick S.; Bhowmick S.; Kilmametov A.; Palit M. (My University, 2025)
The equiatomic FCC CoCuFeMnNi HEA subjected to high pressure torsion (HPT) till 5 turns, showed a fourfold increase in hardness and three orders of magnitude decrease in grain size with an insignificant change in strain rate sensitivity and activation volume. There is a gradual transition from planar slip at low strain to twinning followed by shear banding at high strain accompanied by conversion of low angle to high angle grain boundaries, resulting in average grain size of 55 ± 33 nm at the periphery of 5 turn HPT sample. Atom probe tomography revealed that nano-clusters present in FCC matrix in the homogenized sample underwent partial dissolution during HPT to increase the copper concentration from 8.24 ± 3.29 to 17.02 ± 1.51 atomic%, contributing to significant solid solution strengthening in addition to dislocation and grain size strengthening, leading to tremendous increase in hardness (539 to 1941 MPa). Transient instrumented micro and nano-indentation tests yield activation volume between 12 and 17 b3 for the homogenized and HPT processed samples with three orders of magnitude difference in grain size and dislocation density. This indicates that the dislocation–solute environment interaction is the rate controlling mechanism during the deformation of the investigated HEA. The present work provides a unique pathway to design high entropy alloys that can explore and utilize non-equilibrium solid solution strengthening as a major strengthening mechanism to achieve high strength. © 2023